Improving Motivation And Learning Outcomes In Mathematics Using The Cooperative Learning Model Used By Dakota Media In Grade IV Of SD Negeri 100/II Muara Bungo - Vivi Fitriana Rhamdhani; Puput Wahyu Hidayat; Sundahry Sundahry (Master of Action Research in Mathematics Classroom, 2026)
Mathematics learning in elementary schools still faces various challenges, particularly the low motivation and engagement of students during the learning process. This study aims to improve the motivation, learning process, and learning outcomes of fourth-grade students at SDN 100/II Muara Bungo through the implementation of the Cooperative Learning model, specifically the Teams Games Tournament (TGT), supported by the use of Dakon Matematika media. The research employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were 28 fourth-grade students, and data were collected through teacher and student observation sheets, motivation questionnaires, and achievement tests. The findings revealed significant improvements in all aspects. Teacher performance increased from 92% in the first cycle to 100% in the second cycle, student participation rose from 15.22% to 52.14%, learning motivation improved from 54.54% to 85.71%, and learning achievement mastery increased from 53.57% to 82.14%. These results indicate that the TGT model assisted by Dakon Matematika is effective in enhancing mathematics learning quality, and it can serve as an innovative instructional strategy that is